The Implementation of Islamic Religious Education as A Preventive Measure Against Promiscuity - Fauzi, Arif; Ahmadin, Ahmadin; Jamilah, Sri (Dirasah: Jurnal Pendidikan Islam, 2025)
This research aims to analyze the implementation of Islamic Religious Education as an effort to prevent promiscuity at SMA Negeri 1 Belo. The main issue raised is the role of Islamic Religious Education in shaping students' character and preventing promiscuous behavior that can be detrimental to their development. This research uses a qualitative approach with a case study method, where data is collected through observation, interviews and documentation. The research results show that the implementation of Islamic Religious Education at SMA Negeri 1 Belo has had a positive impact in preventing promiscuity, despite challenges such as the influence of social media and lack of parental involvement. The main supporting factors are the active role of teachers, routine religious activities, and support from the school environment, while inhibiting factors include limited interesting learning methods and lack of external supervision. This research suggests the need to strengthen cooperation between schools, parents and the community to optimize efforts to prevent promiscuity through Islamic Religious Education.